2019
DOI: 10.1007/s42729-019-00105-z
|View full text |Cite
|
Sign up to set email alerts
|

24-Epibrassinolide Improves Root Anatomy and Antioxidant Enzymes in Soybean Plants Subjected to Zinc Stress

Abstract: The aim of this research was to determine whether 24-epibrassinolide can mitigate oxidative stress in soybean plants subjected to different zinc levels; to examine this, we evaluated the possible repercussions on anatomical, nutritional, biochemical, physiological and morphological behaviours. The experiment followed a completely randomized factorial design with two concentrations of 24-epibrassinolide (0 and 100 nM EBR, described as-EBR and + EBR, respectively) and three zinc supplies (0.2, 20 and 2000 μM Zn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 132 publications
(146 reference statements)
1
12
1
Order By: Relevance
“…In order to overcome the limits of detection imposed by the in vivo XRF measurements, it was necessary to increase the dose to 23 g Zn L −1 . High concentrations of Zn may however negatively influence the uptake and transport of other nutrients such as K, P, Mg, Fe, Cu, and Mo (Santos et al 2020). In the present study, interference of Zn supply on the concentration of K, Ca, Mn, and Fe in plant petiolule was not observed, which suggests that even in higher concentrations, Zn was not interfering badly the metabolism of other nutrients.…”
Section: Discussioncontrasting
confidence: 50%
“…In order to overcome the limits of detection imposed by the in vivo XRF measurements, it was necessary to increase the dose to 23 g Zn L −1 . High concentrations of Zn may however negatively influence the uptake and transport of other nutrients such as K, P, Mg, Fe, Cu, and Mo (Santos et al 2020). In the present study, interference of Zn supply on the concentration of K, Ca, Mn, and Fe in plant petiolule was not observed, which suggests that even in higher concentrations, Zn was not interfering badly the metabolism of other nutrients.…”
Section: Discussioncontrasting
confidence: 50%
“…This consistent salt-induced decrease was a result of stomatal closure due to the direct effect of the stress on photosynthetic capacity, such as diffusion of carbon dioxide (CO 2 ) into the leaves [ 51 ]. Stomatal conductance was greatly improved when BL was applied at the BL 4 and BL 5 growth stages, suggesting that the BL enabled CO 2 diffusion to improve stomatal variables and leaf anatomy [ 52 , 53 ], thereby minimizing the negative effects of salinity.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of foliar application of Zn in enhancing grain Zn concentration may be due to Zn mobility in phloem (Zhang et al 2010;Hussain et al 2012). Unlike, Santos et al (2020) reported that high concentrations of Zn may negatively influence the uptake and transport of other nutrients such as K, P, Mg, Fe, Cu, and Mo. Concerning the tolerance of crop to applied herbicides, sulfonylurea herbicides such as pyrazosoulfuron-ethyl, azimsulfuron, and halosulfuron-methyl are among the most widely used compounds for the control of broadleaf weeds and sedges in rice (Takeda et al 1986).…”
Section: •-mentioning
confidence: 99%